Lucinid-associated microbial community divergence in peri-mangrove ecosystems - Shi, Junhui; Guo, Yang; Jin, Shi; Zhao, Kuan; Li, Fei; Zhong, Zhaoshan; Zhang, Huan; Zhang, Jianhua; Wang, Minxiao (Frontiers in Marine Science, 2025)
Mangrove forests are highly productive coastal ecosystems in which microbial communities drive key biogeochemical processes, such as sulfur and carbon cycling. Lucinid clams and their bacterial symbionts, commonly found in organic-rich habitats such as mangrove fringes, can perform chemosynthesis driven by the oxidation of sulfide and can further modify sediment characteristics through their chemosymbiotic and burrowing activities. However, the impact of these activities on sedimentary microbial communities remains unclear. In this study, we collected sediment samples from areas with varying lucinid densities and conducted amplicon sequencing to examine microbial community structure. Our findings demonstrated that microbial diversity and community composition varied considerably with lucinid density. Among the dominant microbial taxa, sulfur-reducing groups such as Desulfobacterales were significantly more abundant in samples from lucinid-rich regions. Furthermore, the abundance of sulfur-reducing functional genes was higher in lucinid-rich regions. These results indicate that the sulfur cycle is more active in these areas, possibly due to the high organic matter content and the presence of chemosymbiotic lucinids. The accelerated sulfur cycle can enhance carbon fixation by lucinid symbionts, highlighting the ecological importance of chemosymbiotic bivalves in peri-mangrove microbial communities.